Biocompatibility of chitosan gel associated with glycerol phosphate for the healing of experimentally induced radial defects in rabbits (Oryctolagus cuniculus) - Minto, B. W. [UNESP]; Borsaro, C. P. [UNESP]; Nobile, M. [UNESP]; Coelho, L. P. [UNESP]; Franco, G. G. [UNESP]; Kawamoto, F. Y. K. [UNESP]; Campos, M. G. N.; Dias, L. G. G. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Tissue engineering is an interdisciplinary science that has been developing biomaterials for bone regeneration in medicine and veterinary medicine, following an imminent need. The aim of this study was to evaluate bone regeneration after use of chitosan hydrogel associated with glycerol phosphate in experimentally induced bone gap in the radius of rabbits. Fifteen adult rabbits were randomly distributed in two experimental groups, represented by each radius of every single animal. The animals in the Biomaterial Group (GB) were treated with a glycerol phosphate-associated chitosan hydrogel and in the Control Group (GC) they received no treatment with the biomaterial. The animals were evaluated clinically, radiographically, histologically and by optic densitometry at 30, 60 and 90 days postoperatively. There was statistical superiority in the general average of the radiographic estimates of GB (2.33 +/- 0.48) over the CG (1.77 +/- 0.06). The general averages of GB densitometric evaluation were higher than the CG, being 6.207 +/- 1.374 and 5.71 +/- 1.512, respectively. Histopathological evaluation of GB was superior to CG in periods of 30, 60 and 90 days. Chitosan hydrogel constitutes a biomaterial of desired characteristics, promoting faster and more efficient bone repair when compared to GC.
Keywords: rabbit; bone regeneration; biomaterials; chitosan